Multiconductor Transmission Line Modeling of Crosstalk Between Cables in the Presence of Composite Ground Planes - Lansink Rotgerink, J.H.G.J.; Serra, R.; Leferink, F. (IEEE, 2021)
Modern transportation systems, such as aircraft, are increasingly replacing metal body parts for composite materials, such as carbon-fiber reinforced plastics. Despite the multiple advantages in terms of weight, size, and fuel consumption, this trend is posing a challenge for protection of cables against electromagnetic interference. Early risk assessment and optimization of cable design in modern aircraft require reliable methods that can quickly and accurately estimate crosstalk behavior in the presence of lossy ground planes. This article presents two novel methods to incorporate such lossy ground planes into the crosstalk modeling of cable bundles. The first method considers the ground plane as a discrete collection of cylindrical conductors. In the second method a ground impedance matrix is derived for lossy ground planes with a finite thickness. Results of both methods are compared to full-wave simulations and measurements, yielding excellent results in terms of accuracy and computation times. The discretized ground plane method is also applied to the case of wire pairs that are enclosed by two ground planes, both aluminum and carbon–fiber reinforced plastic, as a first step towards investigation of wiring that is embedded in thermoplastic material. Once more simulations and measurements are in good agreement.